2013
DOI: 10.3758/s13421-013-0314-9
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional transformation in tests of spatial and environmental cognition

Abstract: In previous research, it has been argued that spatial performance on psychometric tests might be accounted for, in part, by the need for test-takers to transform mentally two-dimensional (2-D) test items into a three-dimensional (3-D) representation. With this in mind, the Landscape Perception Test (LPT) was designed to isolate the 2-D to 3-D (and vice versa) transformational aspect of spatial cognition. Gender differences were used as an indirect means to examine the contribution of the 2-D to 3-D transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…As in the case of our work, these studies considered the degrees of error for establishing comparisons between sexes. Other studies that considered the number of correct answers found no gender differences (Hegarty et al, 2006; Iwanowska and Voyer, 2013; Zancada-Menendez et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…As in the case of our work, these studies considered the degrees of error for establishing comparisons between sexes. Other studies that considered the number of correct answers found no gender differences (Hegarty et al, 2006; Iwanowska and Voyer, 2013; Zancada-Menendez et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…This is a crucial question that requires much research, although initial work by Titze, Heil, and Jansen (2008) seems to rule out the role of task complexity in explaining this reduced gender difference across psychometric and chronometric mental rotation tasks. Other possibilities (e.g., the presence of impossible rotations on the MRT) were raised by Iwanowska and Voyer (2013). In addition, mental rotations tasks might be related to memory load.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the magnitude of gender differences in mental rotation performance was larger for occluded than for nonoccluded items (Bors & Vigneau, 2011;Doyle & Voyer, 2013;Voyer & Doyle, 2010;Voyer & Hou, 2006). This can be interpreted as reflecting the role of the 3D nature of the stimuli in gender differences when processing occluded items (Iwanowska & Voyer, 2013). Subsequent studies found that items with mirror distractors (incorrect response alternatives that are the mirror images of the target item) were more difficult to process than items with structural distractors (incorrect response alternatives that are structurally different from the target item) for both genders, with a greater magnitude of gender differences in accuracy on items with mirror distractors than on items with structural distractors (Bors & Vigneau, 2011;Doyle & Voyer, 2013).…”
mentioning
confidence: 84%
“…One issue that has been brought up with psychometric tests, especially with the MRT, is that it is not a pure measure of mental rotation. For example, it is contaminated by the presence of impossible rotations (Kerkman, Wise, & Harwood, 2000;Iwanowska & Voyer, 2013). Considering these issues, as the present study was concerned with sex differences in the mental rotation process, the focus of the experiment was on chronometric mental rotation.…”
Section: Introductionmentioning
confidence: 98%